The prevalence of infection with head lice pediculus humanus capitis among elementary girl students in Albaha region-Kingdom of Saudi Arabia - Gharsan, Fatehia Nasser; Abdel-Hamed, Naglaa Fekry; Mohammed Elhassan, Somia Abd Alla; Rahman Gubara, Nihad Gubara Abdel (International Journal of Research in Dermatology, 2016)
Background: Head lice infestation with Pediculus humanus capitis is a widespread health concern among school children. The prevalence of lice infestation and the associated risk factors were assessed among primary school girls in Albaha region. Methods: A total of 672 girls in Al Makhwa area were examined and interviewed. The prevalence of pediculosis was 45.45%. Results: The results indicated there was a significant relation between lice infestation and several risk factors: crowdness in classrooms (89.52% in heavily crowded classes); sharing bedrooms (P≤0.001); hair washing frequency and the person washing it (P≤0.001); sharing combs and towels (69.53 and 71.4% respectively); using a hair-dryer (P≤0.001). Girls' school class level, hair characters, family income, number of family members, mother's education and occupation, mode of transport to school and presence of a house servant were found to have no significant impact on head lice infestation. Conclusions: Family education is needed to implement proper personal hygiene practices and cease sharing personal items. Periodic screening of students at school and home is recommended for early detection and treatment.